Human airway-like multilayered tissue on 3D-TIPS printed thermoresponsive elastomer/collagen hybrid scaffolds. (1st September 2020) - Wu, Linxiao; Magaz, Adrián; Huo, Suguo; Darbyshire, Arnold; Loizidou, Marilena; Emberton, Mark; Birchall, Martin; Song, Wenhui
Abstract: Developing a biologically representative complex tissue of the respiratory airway is challenging, however, beneficial for treatment of respiratory diseases, a common medical condition representing a leading cause of death in the world. This in vitro study reports a successful development of synthetic human tracheobronchial epithelium based on interpenetrated hierarchical networks composed of a reversely 3D printed porous structure of a thermoresponsive stiffness-softening elastomer nanohybrid impregnated with collagen nanofibrous hydrogel. Human bronchial epithelial cells (hBEpiCs) were able to attach and grow into an epithelial monolayer on the hybrid scaffolds co-cultured with either human bronchial fibroblasts (hBFs) or human bone-marrow derived mesenchymal stem cells (hBM-MSCs), with substantial enhancement of mucin expression, ciliation, well-constructed intercellular tight junctions and adherens junctions. The multi-layered co-culture 3D scaffolds consisting of a top monolayer of differentiated epithelium, with either hBFs or hBM-MSCs proliferating within the hyperelastic nanohybrid scaffold underneath, created a tissue analogue of the upper respiratory tract, validating these 3D printed guided scaffolds as a platform to support co-culture and cellular organization. In particular, hBM-MSCs in the co-culture system promoted an overall matured physiological tissue analogue of the respiratory system, a promising synthetic tissue for drug discovery, tracheal repair and reconstruction. Statement of Significance: Respiratory diseases are a common medical condition and represent a leading cause of death in the world. However, the epithelium is one of the most challenging tissues to culture in vitro, and suitable tracheobronchial models, physiologically representative of the innate airway, remain largely elusive. This study presents, for the first time, a systematic approach for the development of functional multilayered epithelial synthetic tissue in vitro via co-culture on a 3D-printed thermoresponsive elastomer interpenetrated with a collagen hydrogel network. The viscoelastic nature of the scaffold with stiffness softening at body temperature provide a promising matrix for soft tissue engineering. The results presented here provide new insights about the epithelium at different surfaces and interfaces of co-culture, and pave the way to offer a customizable reproducible technology to generate physiologically relevant 3D biomimetic systems to advance our understanding of airway tissue regeneration. Graphical abstract: Image, graphical abstract